PENGARUH PEMBERIAN PUPUK ORGANIK KOTORAN AYAM DALAM BENTUK PADAT DAN CAIR TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH - Artikan Halawa (Universitas Nias Raya, 2025)
Organic fertilizers have many advantages, including: improving soil structure, maintaining soil fertility, helping plants grow, increasing microbial activity, preventing excess nutrient supply, maintaining soil moisture, increasing soil binding capacity, being safe for plants and the environment, and being inexpensive and readily available. The purpose of this study was to determine the effect of applying organic chicken manure fertilizer in solid and liquid form on the growth of red chili plants. The approach in this study was quantitative with a purely experimental research type. The population and sample in this study were all 96 red chili plants. The data collection techniques used in this study were: (1) Observation; (2) Documentation Study. This study used a factorial Randomized Block Design (RBD) consisting of two factors: the first factor was chicken manure fertilizer in solid form, which consisted of four levels: no treatment (PD0), 1.17 (PD1), 1.76 (PD2), and 2.35 (PD3). The second factor was liquid chicken manure, which consisted of four levels: no treatment (PD0), 40 ml/liter of water (PC1), 60 ml/liter of water (PC2), and 80 ml/liter of water (PC3). Therefore, the conclusion of this study is that the application of solid chicken manure significantly affected the growth of red chili plants, specifically in terms of plant height, leaf number, stem diameter, and branch number. This is because chicken manure contains or provides essential nutrients, improves the soil, and supports the activity of soil microorganisms. However, the application of liquid chicken manure did not significantly affect the growth of red chili plants. This is because the organic fertilizer (POC) from chicken manure is easily washed out of the growing medium and its presence is only temporary. The researchers recommend that farmers utilize organic chicken manure as a substitute for synthetic fertilizers, as it is readily available and environmentally friendly.